2018
DOI: 10.3389/fnagi.2017.00431
|View full text |Cite
|
Sign up to set email alerts
|

Age-Modulated Associations between KIBRA, Brain Volume, and Verbal Memory among Healthy Older Adults

Abstract: The resource modulation hypothesis suggests that the influence of genes on cognitive functioning increases with age. The KIBRA single nucleotide polymorphism rs17070145, associated with episodic memory and working memory, has been suggested to follow such a pattern, but few studies have tested this assertion directly. The present study investigated the relationship between KIBRA alleles (T carriers vs. CC homozygotes), cognitive performance, and brain volumes in three groups of cognitively healthy adults—middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…The threshold was then changed at p < 0.001, uncorrected, with a cluster of 50 contiguous voxels. This threshold was chosen based on a previous study that tested the impact of a genetic risk factor for cognitive impairment on brain volumes; see Stickel et al (2018). The cluster threshold was more conservative than previous VBM analyses from our laboratory using the same p-threshold and a cluster size of 18, which was determined based on Monte Carlo simulations (Walther et al, 2011), but was less conservative than some other VBM analyses using the same p-value (Glodzik et al, 2012: k = 75; ten Kate et al, 2016: k = 100).…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold was then changed at p < 0.001, uncorrected, with a cluster of 50 contiguous voxels. This threshold was chosen based on a previous study that tested the impact of a genetic risk factor for cognitive impairment on brain volumes; see Stickel et al (2018). The cluster threshold was more conservative than previous VBM analyses from our laboratory using the same p-threshold and a cluster size of 18, which was determined based on Monte Carlo simulations (Walther et al, 2011), but was less conservative than some other VBM analyses using the same p-value (Glodzik et al, 2012: k = 75; ten Kate et al, 2016: k = 100).…”
Section: Image Processingmentioning
confidence: 99%
“…It may be that across the relatively wide age range (50-94 years) in the present study, the impact of APOE ε4 status may change with increasing age rather than having a uniform effect among all older adults. Genetic factors that influence cognition appear to have stronger impact in older age prior to the onset of dementia (Lindenberger et al, 2008;Papenberg et al, 2015;Stickel et al, 2018), possibly due to weakening structural integrity and/or impairments in neural processing. Supporting this notion, some have found that the presence of one or more APOE ε4 alleles is linked to poorer cognition, specifically among older adults (Rawle et al, 2018), and cognitive decline (as opposed to baseline cognition) may be more sensitive to differences in the APOE ε4 status (Li et al, 2019).…”
Section: Cognitionmentioning
confidence: 99%
“…Beyond the select MRI modalities reviewed above, at least two studies examined the extent to which certain genotypes contributed to brain or neurocognitive aging in younger-old and oldest-old adults (Papenberg et al, 2015;Stickel et al, 2018). Two genes of particular interest are COMT (Catechol-O-Methyltransferase), which is implicated in neuromodulation of the prefrontal cortex and executive functions, and KIBRA, which is named for its role in producing proteins expressed in the kidneys and brain.…”
Section: Other Mri Modalitiesmentioning
confidence: 99%
“…It has been speculated, that the lack of consensus across studies stem from age-related neuropathological changes on memory performance, which may interact with polymorphisms such as KIBRA and CLSTN2, the so-called “resource modulation hypothesis” (40, 44). Supporting evidence comes from studies taking age, increased risk for specific diseases and pre-existing diseases into account (9, 10, 46).…”
Section: Canonical Hippo Pathway Links To Srpdsmentioning
confidence: 99%
“…Supporting evidence comes from studies taking age, increased risk for specific diseases and pre-existing diseases into account (9, 10, 46). Stickel et al (40) report, that KIBRA results in decreased verbal memory performance and lower brain volumes in CC homozygotes compared to T carriers, particularly among older persons (40). In individuals with unipolar depression, Pantzar et al (10) showed an interactive effect of KIBRA and CLSTN2 polymorphisms on memory performance, but not in older individuals without depression (10).…”
Section: Canonical Hippo Pathway Links To Srpdsmentioning
confidence: 99%